998. Understanding Retention in PrEP Care in the South: Insights from an Academic HIV Prevention Clinic. (31st December 2020) - Burns, Charles; Borges, Monica; Frye, Justin; Keicher, Kathryn V; Elliott, Scotty; Schwartz, Sheila K; Shipp, Kenneth W; Okeke, Nwora L; McKellar, Mehri; McKellar, Mehri
Abstract: Background: Daily emtricitabine-tenofovir disoproxil fumarate has emerged as one of the most effective tools to prevent HIV transmission. However, it remains poorly utilized in the South. We report on PrEP retention in care and sexually transmitted infections (STIs) in a large academic PrEP clinic in Durham, North Carolina. Methods: We conducted a retrospective chart review of patients in the Duke University PrEP Clinic from Jan. 1, 2015 through Oct. 15, 2019. Short-term retention in care was completion of a 3 month (mo) follow up as per CDC guidelines. Long-term retention was defined as completion of a 3 mo visit and an additional visit between 8 and 12 mo. Baseline STI was defined as a diagnosis at or within 1 year prior to initial PrEP visit. STI diagnosis while on PrEP was any subsequent diagnosis while retained in care. Odds ratios (OR) were generated using multivariable logistic regression. Kaplan-Meier curves were generated for retention in care and compared using the log rank test. Results: A total of 255 patients attended at least one PrEP clinic encounter; 89% were men, 37% were Black, and 73% identified as men who have sex with men (MSM); 153 (60%) returned for at least one follow-up visit. Short and long term retention in care were met by 130/237 (55%) and 80/217 (37%) patients respectively. OR for retention are reported in Table 1. MSM are more likely to be retained in the short-term (OR 5.22 [95% confidence interval (CI) 1.57-17.32]). Self-referred patients were more likely to be retained in the long-term (OR 2.18 [95% CI 1.12-4.23]). Patients without insurance were less likely to attain long-term retention in care outcomes (OR 0.32 [95% CI 0.11-0.91]). STI diagnoses include 30 (12%) patients for a total of 42 unique infections at baseline and 44 (17%) for a total of 69 unique infections at follow up. Two new HIV diagnoses were made at first PrEP clinic encounter with no new diagnoses made at follow-up. Baseline STI was not associated with retention in care over time with disengagement defined as 6 mo post last visit (Figure 1). Table 1) Odds Ratios of Retention in Care at 3 and 12 Months Figure 1) Retention in Care for Patients with Baseline STI Diagnosis. Conclusion: Our PrEP clinic shows a decline in patient retention over time. STIs were also prevalent, reinforcing that frequent STI testing and counseling should be part of each PrEP encounter. Further investigations into how to increase and improve PrEP utilization for HIV prevention are needed. Disclosures: All Authors : No reported disclosures